PENGARUH INTELLECTUAL CAPITAL TERHADAP PRICE BOOK VALUE MELALUI LABA PERUSAHAAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI TAHUN 2011-2013 - Purnamasari, Puji Endah (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2017)
The purpose of this study is to examine the Intellectual Capital to Price Book Value through the Company's Profit calculated by measuring Return On Equity (ROE) and Return On Asset (ROA), so it can be described for the following problem formulation: (1) test the partial intellectual (3) testing the effect of intellectual capital on PBV through ROE, (4) testing the effect of intellectual capital on PBV through ROA. While the population of this study are all banking companies listed on the BEI 2011-2013. Determination of the sample is done by using purposive sampling method to obtain 18 banking companies listing in BEI period 2011-2013. The type of data used is quantitative and is secondary data obtained from Indonesian Capital Market Directory (ICMD) in 2011-2013. Data analysis using path  analysis technique (path analysis). The results of this study explain that (1) intellectual  capital has a significant positive effect on PBV, ROE and ROA, (2) ROE and ROA have a significant positive effect on PBV, (3) intellectual capital influence on PBV through ROE,(4) intellectual capital PBV through ROA. So the result of path analysis showed that Intellectual Capital influences PBV through ROE and ROA. ROE and ROA status as intervening variable that acts as a booster for the direct relationship of intellectual capital to PBV in banking companies listing on BEI 2011-2013. keywords: Intellectual Capital (IC), Price Book Value (PBV), Return On Equity (ROE) dan Return On  Asset (ROA).